STUDI KELAYAKAN PANTAI SAWARNA SEBAGAI DESTINASI WISATA UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT SETEMPAT - Najah Savira, Anjali; Assegaff, Mahani; Syania, Lasti; Furqon, Chudamul; Marseli, Febriana; Hendra Gunawan, Bastian; Lutfiah Maghningtias, Afirrah (Penerbit Lafadz Jaya, 2023)
Most of the coastal areas in Indonesia are natural areas that have potential tourism and not yet developed optimally, one of which is the coastal area of Sawarna who is in the Banten. Tourist activities in this area have long been underway, and coastal areas Sawarna have a spacious and beautiful beach area with rocks that become one of the attractions of tourism. This research aims to find out and explain the role of human resources in tourism development on the beach of Sawarna. Method qualitative descriptive analysis is used in this study. And the data collection method performed namely through observation, document analysis, interview results and library studies as data Collection Instrument. Based on the results of research can be concluded that tourism in Indonesia, it has a large role as an economic driver. Society in the region tourism is a human resource that has an important role in contributing to improving tourism in the area. The role of human resources in the development of tourism in the coastal area of Sawarna is an aspect of success in doing development of existing tourist potential.